Reversal of fibronectin and opsonic deficiency in patients. A controlled study. - Saba, T M (1984)
Plasma fibronectin is an opsonic glycoprotein which augments reticuloendothelial phagocytic clearance of nonbacterial particulates. We evaluated the influence of intravenous infusion of plasma cryoprecipitate on circulating immunoreactive fibronectin and associated opsonic activity at 0.5, 2.0, 4.0, 10, and 21 hr postinfusion in septic (n = 8) and nonseptic (n = 6) surgical and/or trauma patients with documented plasma fibronectin deficiency. The study was a randomized, double-blind, crossover clinical protocol in which fibronectin-poor (0.116 +/- 0.025 mg/ml) cryoprecipitate extracted plasma (placebo) was compared to fibronectin-rich (2.139 +/- 0.161 mg/ml) plasma cryoprecipitate. Septic injured patients (149.37 +/- 17.11 micrograms/ml) had lower (p less than 0.05) plasma fibronectin levels than nonseptic injured patients (212.17 +/- 7.14 micrograms/ml) and both were less (p less than 0.05) than normal (330 +/- 30 micrograms/ml). As tested in vitro with a peritoneal macrophage monolayer assay, cryoprecipitate manifested opsonic activity related to its fibronectin concentration. Intravenous infusion of fibronectin rich cryoprecipitate reversed both the immunoreactive fibronectin and opsonic deficiency, while infusion of the placebo at a comparable total protein load did not reverse either deficient parameter. Reversal of fibronectin deficiency was more sustained in nonseptic injured patients as compared to septic injured patients. Thus, reversal of opsonic deficiency in septic and nonseptic injured patients is observed after infusion of plasma cryoprecipitate and not with infusion of fibronectin deficient plasma at comparable protein loads. Also, cryoprecipitate extracted plasma may serve as an appropriate control solution for randomized studies evaluating the therapeutic value of fibronectin-rich plasma cryoprecipitate.